2021
DOI: 10.1111/syen.12461
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny of the tribe Empoascini (Hemiptera: Cicadellidae: Typhlocybinae) based on morphological characteristics, with reclassification of the Empoasca generic group

Abstract: A morphology‐based phylogenetic analysis of the tribe Empoascini (Hemiptera: Cicadellidae: Typhlocybinae) is presented for 58 of 83 formerly recognized genera based on 99 morphological characters of adults. The results support excluding the New World Beamerana generic group from Empoascini. The remaining genera of Empoascini were recovered as a monophyletic sister group of Dikraneurini. Previously recognized tribes Jorumini and Helionini are derived from within Empoascini and are considered synonyms of the lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 42 publications
(64 reference statements)
0
19
0
Order By: Relevance
“…Inter-tribe relationships of the five monophyletic tribes are identical to the one obtained in the Anchored Hybrid Enrichment (AHE) based phylogenomics [6], with Alebrini sister to Empoascini as the basal branch, followed by the branch of Dikraneurini sister to Erythroneurini, and finally the branch with members of Typhlocybini and Zyginellini, indicating the relationships among the five monophyletic tribes are to some extent stable. It is different from the sister-group relationship of Empoascini to Dikraneurini that proposed by Zhang (1990) and Xu (2021) based on morphological data and Dikraneurini to Typhlocybini and Zyginellini proposed by Chen (2021) based on molecular data [9,57,61]. Inter-tribe relationships of the five monophyletic tribes are identical to the one obtained in the Anchored Hybrid Enrichment (AHE) based phylogenomics [6], with Alebrini sister to Empoascini as the basal branch, followed by the branch of Dikraneurini sister to Erythroneurini, and finally the branch with members of Typhlocybini and Zyginellini, indicating the relationships among the five monophyletic tribes are to some extent stable.…”
Section: Phylogenetic Relationshipsmentioning
confidence: 84%
“…Inter-tribe relationships of the five monophyletic tribes are identical to the one obtained in the Anchored Hybrid Enrichment (AHE) based phylogenomics [6], with Alebrini sister to Empoascini as the basal branch, followed by the branch of Dikraneurini sister to Erythroneurini, and finally the branch with members of Typhlocybini and Zyginellini, indicating the relationships among the five monophyletic tribes are to some extent stable. It is different from the sister-group relationship of Empoascini to Dikraneurini that proposed by Zhang (1990) and Xu (2021) based on morphological data and Dikraneurini to Typhlocybini and Zyginellini proposed by Chen (2021) based on molecular data [9,57,61]. Inter-tribe relationships of the five monophyletic tribes are identical to the one obtained in the Anchored Hybrid Enrichment (AHE) based phylogenomics [6], with Alebrini sister to Empoascini as the basal branch, followed by the branch of Dikraneurini sister to Erythroneurini, and finally the branch with members of Typhlocybini and Zyginellini, indicating the relationships among the five monophyletic tribes are to some extent stable.…”
Section: Phylogenetic Relationshipsmentioning
confidence: 84%
“…In Empoascini, all genera have ocelli, except Beamerana and Paulomanus . The latter genera, which have hind wing venation identical to that of many Empoascini, nevertheless grouped with Typhlocybini in a recent morphology‐based phylogeny and were tentatively placed in the latter tribe (Xu et al, 2021 ). Few genera in Typhlocybini have ocelli, for example, Hiratettix and Caknesia , but we were able to include only the former in our analyses and it occupies a relatively derived position within the tribe, suggesting that ocelli were lost and regained at least once in this tribe (Figure 4a ).…”
Section: Discussionmentioning
confidence: 99%
“…Beamerana and Paulomanus. The latter genera, which have hind wing venation identical to that of many Empoascini, nevertheless grouped with Typhlocybini in a recent morphology-based phylogeny and were tentatively placed in the latter tribe (Xu et al, 2021).…”
Section: Mitogenome Featuresmentioning
confidence: 93%
“…In our search of the literature, we found 10 publications that listed noteworthy records of 17 species that are specified as being either documented by individual citizen scientists (1 species; McKamey and Sullivan-Beckers, 2019) or contributions made to online citizen science platforms in North America (BugGuide or Hopper Site; Table 1). We also located one publication (Leavengood et al, 2017) containing a noteworthy record that was found by a member of the public but a These species are currently unplaced within the tribe Empoascini, as they were not treated in the latest revision of the tribe (Xu et al, 2021), which redefined its component genera. b This publication was not found in our initial search of the literature, since it does not include any reference to citizen science, and instead was found when we were looking for information on the year this species was introduced in California.…”
Section: Value Of Citizen Science In the Knowledge Of Hoppers Based On Literature Reviewmentioning
confidence: 99%